Studies on the reaction mechanism of soybean callus succinyl CoA synthetase. phosphorylation of the enzyme on immobilized adenosine-triphosphate and enzyme attached to a solid support - de Xifra, E.A.W. (1972)
Fil:del C. Batlle, A.M. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.